Adaptive look-ahead routing for low latency network-on-chip - Al Areqi, Nadera Najib Qaid (2014)
Network-on-chipsto employ simple oblivious routing algorithms, such as dimension order routing (DOR). While such oblivious routing algorithms are easy to implement in hardware, they often inefficient job of balancing the load across the links. Adaptive routing algorithms offer the ability to avoid congestion by supporting multiple paths between a source and destination. However, supporting adaptive routing for low latency routers is a challenge due to the computation of routing algorithm in one router in advanced (look-ahead routing). In this work we present an RTL architecture for adding adaptive look-ahead routing algorithm to a recently proposed low latency, virtual channel wormhole NoC router. In our proposed design each router pre-compute the preferred output port based on its local congestion and transfer the preferred output ports to the neighbor routers. These preferred output ports are used in the look-ahead routing. We compared our propose adaptive routing architecture with the reference design look-ahead routing XY routing algorithm under Transpose traffic and obtained 15 % improvement in average latency per hop. Our proposed routing algorithm has negligible influence in area overhead (12% ) while has no influence on maximum operation frequency.